2015
DOI: 10.1016/j.neuroimage.2015.03.080
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the dynamic relationship between cerebral blood flow and the BOLD signal: Implications for quantitative functional MRI

Abstract: Calibrated BOLD imaging, in which traditional measurements of the BOLD signal are combined with measurements of cerebral blood flow (CBF) within a BOLD biophysical model to estimate changes in oxygen metabolism (CMRO2), has been a valuable tool for untangling the physiological processes associated with neural stimulus-induced BOLD activation. However, to date this technique has largely been applied to the study of essentially steady-state physiological changes (baseline to activation) associated with block-des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 52 publications
3
19
1
Order By: Relevance
“…The important influence of viscoelastic effects suggests that classic block designs induce steady-state dynamics with a slow HRF, whereas uncoupling of CBF and CBV during dynamic neural activity leads to a sharper HRF and stronger frequency response. Although we could not directly measure the CBF responses to these fast oscillations because of the limited temporal resolution and sensitivity of arterial spin-labeling methods, previous experiments have demonstrated that the CBF-CBV coupling is altered during dynamic stimulation (43) and have suggested that the CBV lags during dynamic neural activity; this suggestion is consistent with our proposed model. Further studies will be needed to assess the mechanism underlying our results more conclusively.…”
Section: Discussionsupporting
confidence: 87%
“…The important influence of viscoelastic effects suggests that classic block designs induce steady-state dynamics with a slow HRF, whereas uncoupling of CBF and CBV during dynamic neural activity leads to a sharper HRF and stronger frequency response. Although we could not directly measure the CBF responses to these fast oscillations because of the limited temporal resolution and sensitivity of arterial spin-labeling methods, previous experiments have demonstrated that the CBF-CBV coupling is altered during dynamic stimulation (43) and have suggested that the CBV lags during dynamic neural activity; this suggestion is consistent with our proposed model. Further studies will be needed to assess the mechanism underlying our results more conclusively.…”
Section: Discussionsupporting
confidence: 87%
“…Increases in neuronal signaling lead to increases in metabolic rate as well as cerebral blood flow (CBF) to deliver more oxygen and glucose to meet the increased demand. The increases in CBF and anaerobic glucose metabolism are greater than the increase in oxidative metabolic rate (Fox et al, 1988), leading to a higher blood oxygen concentration and resultant changes in the blood-oxygenation-level dependent (BOLD) signal (Simon and Buxton, 2015). Measurement of the BOLD signal is utilized in phMRI to quantify the effects of drugs on neuronal signaling (Leslie and James, 2000).…”
Section: Pharmacological Imaging Methodsmentioning
confidence: 99%
“…In a subsequent work, Wu et al ( 2009 ) obtained functional connectivity maps using CMRO 2 time series derived from simultaneous BOLD and CBF time series acquired with ASL. Although the CMRO 2 time courses were estimated assuming the steady-state biophysical BOLD model, that might have some limitations in a more dynamical situation (Simon and Buxton, 2015 ), the strong similarity observed by Wu et al ( 2009 ) between functional connectivity maps obtained from BOLD, CBF and CMRO 2 time courses added further evidence to a significant BOLD-CBF coupling during resting state. In a recent work the study of dynamic BOLD-CBF relationship during resting state was addressed with significant methodological improvements, including physiological noise correction in the tag and control ASL images and taking into account the influence of global cardiac fluctuations (Tak et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative calibration techniques without gas administration have also been proposed based on particular MRI acquisition sequences or breath-hold tasks (Kastrup et al, 1999 ; Fujita et al, 2006 ; Bulte et al, 2009 ; Blockley et al, 2012 , 2015 ). Nevertheless, the calibrated BOLD technique has been mostly applied and validated in studies using block paradigms, and its extension to more dynamic experimental designs is not straightforward (Kida et al, 2006 ; Simon and Buxton, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation